1994
DOI: 10.1002/bdm.3960070206
|View full text |Cite
|
Sign up to set email alerts
|

Psychological determinants of decision attitude

Abstract: Decision attitude — an analog of risk attitude — is the propensity to make (or avoid making) a decision: in decision aversion, a person finds it more desirable to receive through fiat the better of two options than to have a choice between them; in decision seeking, the choice is more desirable, even though it can lead to nothing better than the best option. Both decision aversion and decision seeking were found in hypothetical scenarios. Experimental manipulations and subjects' justifications point to anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
130
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(136 citation statements)
references
References 19 publications
4
130
0
2
Order By: Relevance
“…Feedback could result in regret or rejoicing, thus their curiosity could be rewarded or punished. On average, however, our data indicated that anticipated regret weighs heavier than anticipated rejoicing (see also Beattie et al, 1994, andLarrick &.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Feedback could result in regret or rejoicing, thus their curiosity could be rewarded or punished. On average, however, our data indicated that anticipated regret weighs heavier than anticipated rejoicing (see also Beattie et al, 1994, andLarrick &.…”
Section: Discussionmentioning
confidence: 71%
“…This prediction is based on the finding that people are, in general, more influenced by negative information than by positive information (Taylor, 1991) and on Kahneman and Tversky's (1979) conclusion that losses loom larger than gains. Moreover, recent research by Beattie, Baron, Hershey, and Spranca (1994) found that while decisions are influenced by the anticipation of regret, there was no consistent support for the anticipation of rejoicing as a decision motive. Thus, for most individuals, in weighing regret and rejoicing, we expect the balance to be in favor of regret.…”
mentioning
confidence: 91%
“…First, we may avoid deciding as a consequence of anticipated regret (cf. Beattie et al, 1994). We can do this simply in order to avoid making the wrong decision.…”
Section: Regret In¯uences Behavior Because It Is Anticipated and Becamentioning
confidence: 99%
“…Anticipations of these emotional reactions may in¯uence what we choose, which particular house, movie, or cash register, but also how we choose. That is, negative emotions may prompt us to delay decisions (Beattie et al, 1994) and in¯uence the amount and direction of pre-decisional information search (Luce, 1998). Thus, when making decisions we not only predict the utility that will be provided by these options, as assumed in rational choice theory, we also predict the emotions that arise from comparing the result of that option with the results of options forgone.…”
mentioning
confidence: 99%
“…These emotions are more utilitarian, that is, they are more related to the hedonic value of decision outcomes or events. This presumably is why disappointment and (in particular) regret have attracted so much attention in research on individual decision-making (see e.g., Beattie et al, 1994;Bell, 1982Bell, , 1985Gull, 1991;Kelsey, á Schepanski, I991;Inman, Dyer, 8c Regrer und disuppoimnrenr 3 Jia, 1997;Inman, á McAlister, 1994;Janis á Mann, 1977;Josephs, Larrick, Steele, á Nisbett, 1992;Larrick, 8r. Boles, 1995;Loomes 8c Sugden, 1982, 1986, 1987Mellers, Schwartz, Ho,~Ritov, 1997;Richard, van der Plig[, á de Vries, 1996;Ritov, 1996;Ritov, 8c Baron, 1995;Taylor, 1997;van Dijk, 8c van der Pligt, 1997;Zeelenberg et al, I996;Zeelenberg, 8c Beattie, 1997;Zeelenberg, van der Pligt, óc Manstead, nt press).…”
mentioning
confidence: 99%